Modes and challenges in sports talent identification at senior high schools in Upper East Region, Ghana - Daniel Apaak; Christopher Akubah; Richard Samuel Kwadwo Abieraba (Sport TK, 2024)
Although there are athletic programmes at the senior high schools in the Upper East Region, the question is whether there are certain institutionalised programmes that help identify athletic talent and facilitate the development of student-athletes to the top of their athletic careers. This study was aimed at examining modes and challenges in sports talent identification in Senior High Schools (SHSs) in the Upper East Region (UER) of Ghana. In this cross-sectional study, 203 sports coaches (100 men and 80 women sports coaches) in SHSs in the UER participated in the investigation. These group of individuals were chosen for the investigation since the core responsibility of identifying and developing sports talents lies with them. Data was collected using a questionnaire from which generalisation could be made about modes and challenges in sports talent identification. Descriptive statistics such as frequencies and percentages were calculated using SPSS version 25 (data analysis software). The results of the study revealed that the common mode of identifying talented student-athletes was through observation by coaches (90.6%). Also, limited financial resources (82.3%), judging coaches’ competence by their teams’ performance in competitions (73.9%), and early talent identification (69.0%) were identified as major challenges in sports talent identification. In conclusion, most coaches employ the natural selection method in identifying sports talents, therefore, many sports talents in Senior High Schools in Upper East Region are over looked because they are not currently participating in the sports. Adequate financial resources are not allocated for sports talent identification in SHSs in the UER and much focus is placed on winning SHS competitions to the detriment of recognizing the potential for future success in sports performance among student-athletes.